2018
DOI: 10.5812/iranjradiol.16801
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Feasibility Assessment of T3 Sub-Stage in Rectal Cancer Using MRI

Abstract: Background: MRI predicted distance of mesorectal extension (mrDME) in rectal cancer is one of the independent risk factors for recurrence and poor overall survival. In T3 rectal cancer, if no lymph node or distant metastasis is seen, the selection of optimum treatment is based on the distance of mesorectal extension. Therefore, it is very crucial to investigate the reproducibility of DME in T3 rectal cancer. Objectives: To investigate the reproducibility of the distance of mesorectal extension by tumor invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…32,33 Recently, the use of 5 mm as a cutoff value to differentiate early and advanced rectal cancer is highly accepted. 34 Some studies concluded that the tumors with distance of mesorectal extension .5 mm have poor prognosis compared with \5 mm. 16,35 Many previous studies have investigated the prognosis of T3 subdivision using various cutoff points (4, 5, and 6 mm) and have concluded that the deeper the tumor invasion is, the worst the prognosis becomes.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Recently, the use of 5 mm as a cutoff value to differentiate early and advanced rectal cancer is highly accepted. 34 Some studies concluded that the tumors with distance of mesorectal extension .5 mm have poor prognosis compared with \5 mm. 16,35 Many previous studies have investigated the prognosis of T3 subdivision using various cutoff points (4, 5, and 6 mm) and have concluded that the deeper the tumor invasion is, the worst the prognosis becomes.…”
Section: Discussionmentioning
confidence: 99%
“…The mrDME was noted and was substaged into an early T3 tumor (tumor extension <5 mm beyond the muscularis propria) or an advanced T3 tumor (tumor extension >5 mm beyond muscularis propria). 15,16 mrEMVI was then evaluated and defined as mrEMVI-positive or mrEMVI-negative depending on the radiologic features using the mrEMVI scoring system. The mrEMVI score was determined using several factors such as the pattern of tumor margin, the location of vessel relative to the tumor, the size of vessel, and caliber of vessel as proposed by Smith et al 1 (Figures 2 and 3).…”
Section: Methodsmentioning
confidence: 99%